Efeito do sistema de fermentação, da adição de etanol ao tratamento ácido e da contaminação por Lactobacillus sp na produção de etanol - Costa, Marcelo Augusto de Souza (Universidade Federal de São Carlos, 2017)
The fermentation is one of the most critical steps of the fuel ethanol production. Some factors directly influence the fermentation efficiency, such as the fermentation system, the selected yeast and the bacterial contamination, especially from the genus Lactobacillus. For the control of the contamination, the industries apply antibiotics and biocides, however, these products can result in increased cost and environmental problems for the industry. The use of the acid treatment (sulphuric acid solution, pH 2.0) of the cells between the cycles of fermentation is not always effective to combat the bacterial contamination. In this context, the present study aimed to evaluate the effect of fermentation system – simple batch and fed batch – on the contamination of the sugarcane juice with Lactobacillus sp, in a cell-recycled fermentation with the selected yeast strain of S. cerevisiae PE-2. Following, the effect of ethanol addition to the acid treatment was evaluated to control the bacterial growth in fed-batch system with cell recycle. In the fed-batch system, a higher ethanol production and efficiency was verified, as well as a higher logarithmic variation of the yeast growth. The bacterium L. fermentum was more harmful to the fermentation than L. plantarum, resulting in more sugar left in the fermented must and lower fermentative efficiency, in both systems. The effect of contaminations in the single batch system was higher than in the fed-batch system especially since the substrate feeding allowed a better yeast development, which could be more competitive with the contaminant bacterium. Regarding the modification in the acid treatment performed between the fermentative cycles, only with the acid treatment, the population of L. fermentum reduced almost 3 log cycles at the end of the sixth fermentative cycle, however, when 5% of ethanol was added to the acid solution, the bacterium lost completely the cell viability right after the first fermentative cycle. There was no alteration in the ethanol production in the fermentation contaminated with L. fermentum, comparing the cell treatments with and without the addition of 5% ethanol. The acid treatment + 5% ethanol was able to reduce the population of L. fermentum without impact to the fermentative efficiency and with a low residual sugar concentration in the fermentative must (around 4 g/100 mL), at the end of six ninehour fermentative cycles, in fed-batch system.
Effect of the fermentation system, the addition of ethanol to the acid treatment and the contamination by Lactobacillus sp on the ethanol production
Keywords: Batelada alimentada; Bactéria contaminantes; Lactobacillus fermentum; Lactobacillus plantarum; Saccharomyces cerevisiae; Fed-batch; Bacterial contamination; CIENCIAS AGRARIAS